2014
DOI: 10.1016/j.athoracsur.2014.04.015
|View full text |Cite
|
Sign up to set email alerts
|

A Multifaceted Approach to the Management of Plastic Bronchitis After Cavopulmonary Palliation

Abstract: Background Plastic bronchitis is a rare, potentially life-threatening complication after Fontan operation. Hemodynamic alterations (elevated central venous pressure and low cardiac output) likely contribute to the formation of tracheobronchial casts composed of inflammatory debris, mucin, and fibrin. Pathologic studies of cast composition support medical treatment with fibrinolytics such as inhaled tissue plasminogen activator (t-PA). Methods Retrospective case series of medical, surgical, and catheter-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 25 publications
(31 reference statements)
2
49
0
Order By: Relevance
“…16 The symptoms of plastic bronchitis can be mitigated by using aerosolized tissue plasminogen activator, which acts as an airway clearing agent by effectively breaking down cast material that can then be more easily passed. 17 Aggressive treatment with pulmonary vasodilator agents such as sildenafil or bosentan may theoretically lower impedance to forward passive cavo-pulmonary flow, thereby placing the circulation at a point just beneath the threshold for protein spillage and has been an important component of the treatment strategy for both plastic bronchitis and PLE.…”
Section: Luminal Protein Loss Syndromes and The Lymphatic Systemmentioning
confidence: 99%
“…16 The symptoms of plastic bronchitis can be mitigated by using aerosolized tissue plasminogen activator, which acts as an airway clearing agent by effectively breaking down cast material that can then be more easily passed. 17 Aggressive treatment with pulmonary vasodilator agents such as sildenafil or bosentan may theoretically lower impedance to forward passive cavo-pulmonary flow, thereby placing the circulation at a point just beneath the threshold for protein spillage and has been an important component of the treatment strategy for both plastic bronchitis and PLE.…”
Section: Luminal Protein Loss Syndromes and The Lymphatic Systemmentioning
confidence: 99%
“…It is now understood that the capacity of a patient's lymphatic circulation to drain the increased production of lymph after Fontan completion is determining some of their outcomes [9]. Patients with protein-losing enteropathy and plastic bronchitis have been found to have inadequate lymphatic drainage [16,17]. It has been suggested that patients' lymphatic circulation could be categorized before Fontan completion, and those patients with an already engorged lymphatic circulation would have worse outcomes.…”
Section: Commentmentioning
confidence: 99%
“…The true prevalence of PB is unknown, as it is likely that many patients with mild forms of the disease are undiagnosed. 16,25 Many clinicians are unfamiliar with the disease and may fail to recognize milder forms of the syndrome. 3 In the current study, during admission, only two children had tachycardia, and all other cases showed no signs or symptoms of hypoxia, suggesting that they might be milder forms of PB.…”
mentioning
confidence: 99%